2021
DOI: 10.3389/fpubh.2021.770111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Rumor Debunking Effectiveness During the COVID-19 Pandemic Crisis: Utilizing User Stance in Comments on Sina Weibo

Abstract: Background: The spread of rumors related to COVID-19 on social media has posed substantial challenges to public health governance, and thus exposing rumors and curbing their spread quickly and effectively has become an urgent task. This study aimed to assist in formulating effective strategies to debunk rumors and curb their spread on social media.Methods: A total of 2,053 original postings and 100,348 comments that replied to the postings of five false rumors related to COVID-19 (dated from January 20, 2020, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…In the early phases of the pandemic, the government used Weibo post data to determine the outbreak's stage of development, allowing them to take proper steps (23). According to an analysis of Chinese Weibo user postings, it can be found that the method for debunking rumors varies based on the type of rumor (24). In Macau, different levels of information disclosure to varying epidemic stages through the government's Facebook have effectively addressed the public health crisis (25).…”
Section: Introductionmentioning
confidence: 99%
“…In the early phases of the pandemic, the government used Weibo post data to determine the outbreak's stage of development, allowing them to take proper steps (23). According to an analysis of Chinese Weibo user postings, it can be found that the method for debunking rumors varies based on the type of rumor (24). In Macau, different levels of information disclosure to varying epidemic stages through the government's Facebook have effectively addressed the public health crisis (25).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al introduced the first real-time rumor debunking algorithm for social media [ 41 ]. Wang et al divided rumor debunking methods into six categories (i.e., denial, further fact-checking, refutation, person response, organization response, and combination methods), of which the refutation method has the best debunking effect [ 42 ]. Other researchers tried to find out influencing factors related to rumors.…”
Section: Discussionmentioning
confidence: 99%
“…These rumor-combating behaviors may occur in different stages of rumor spreading (Chen et al. , 2018; Wang and Zhuang, 2018) and have different governance effects and occurrence frequencies (Wang and Zhuang, 2018; Wang et al. , 2021).…”
Section: Importance Of Developing a Typology Of Rumor-combating Behav...mentioning
confidence: 99%
“…Usually, official verification and refutation reports appear after false rumors have been widely circulated, resulting in much misinformation not being corrected in time (Tang et al, 2021). Even when debunking messages are sometimes released, these facts often reach a narrow audience and cannot be effectively disseminated (Wang et al, 2021). Moreover, only the most widespread rumors typically attract attention from authorities and mainstream media (Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation